(untitled) (Nigerian Journal of Technology, 2019)
This research was carried out to ascertain the relationship between effective reservoir management and hydropower station performance selecting the Jebba Hydroelectric Power Station as a case study. In order to achieve this, the daily inflow and outflow data, as well as the generated energy were collected for the reviewed period (2009 – 2016). The hydrological data indicated that during period under study, the reservoir is recovering at a very low rate. A further analysis was carried out by comparing the conversion efficiency of the energy in flowing water and actual energy generated. Thus the product of the head (metres) and the outflow was plotted against the actual energy generated. The results satisfied a linear relationship having a correlation coefficient of 0.7059 which reinforces the knowledge of the effects of hydropower reservoir management on energy generation. http://dx.doi.org/10.4314/njt.v38i3.28